The 2011 unrest at Katla volcano: Characterization and interpretation of the tremor sources - SGATTONI, GIULIA; Ógudmundsson, Ó. Gudmundsson; Einarsson, P.; LUCCHI, FEDERICO; Ka, Lok Li; Sadeghisorkhani, H.; Roberts, R. (Journal of Volcanology and Geothermal Research, 2017)
A 23-hour tremor burst was recorded on July 8–9th 2011 at the Katla subglacial volcano, one of the most active and hazardous volcanoes in Iceland. Thiswas associated with deepening of cauldrons on the ice cap and a glacial flood that caused damage to infrastructure. Increased earthquake activity within the caldera started a few days before and lasted for months afterwards and new seismic activity started on the southern flank. No visible eruption broke the ice and the question arose as to whether this episode relates to a minor subglacial eruption with the tremor being generated by volcanic processes, or by the flood. The tremor signal consisted of bursts with varying amplitude and duration.We have identified and described three different tremor phases, based on amplitude and frequency features. A tremor phase associatedwith the floodwas recorded only at stations closest to the river that flooded, correlating in timewith risingwater level observed at gauging stations. Using back-projection of double cross-correlations, two other phases have been located near the active ice cauldrons and are interpreted to be caused by volcanic or hydrothermal processes. The greatly increased seismicity and evidence of rapid melting of the glacier may be explained by a minor sub-glacial eruption. A less plausible interpretation is that the tremor was generated by hydrothermal boiling and/or explosions with no magma involved. This may have been induced by pressure drop triggered by the release of water when the glacial flood started. All interpretations require an increase of heat released by the volcano.